A cold responsive ethylene responsive factor from Medicago falcata confers cold tolerance by up‐regulation of polyamine turnover, antioxidant protection, and proline accumulation. (10th January 2018) - Zhuo, Chunliu; Liang, Lu; Zhao, Yaqing; Guo, Zhenfei; Lu, Shaoyun
Abstract: Ethylene responsive factor (ERF) subfamily transcription factors play an important role in plant abiotic and biotic stress tolerance. A cold responsive ERF, MfERF1, was isolated from Medicago falcata, an important forage legume that has great cold tolerance. Overexpression of MfERF1 resulted in an increased tolerance to freezing and chilling in transgenic tobacco plants, whereas down‐regulation of the ortholog of MfERF1 in Medicago truncatula resulted in reduced freezing tolerance in RNAi plants. Higher transcript levels of some stress responsive genes ( CHN50, OSM, ERD10C, and SAMS ) and those involved in spermidine (Spd) and spermine (Spm) synthesis ( SAMDC1, SAMDC2, SPDS1, SPDS2, and SPMS ) and catabolism ( PAO ) were observed in transgenic plants than in wild type. However, neither Spd nor Spm level was accumulated in transgenic plants as a result of promoted polyamine oxidase activity. Transgenic plants had higher activities of antioxidants associated with the induced encoding genes including Cu, Zn‐SOD, CAT1, CAT2, CAT3, and cpAPX and accumulated more proline associated with induced P5CS and reduced PROX2 transcription as compared with wild type. The results suggest that MfERF1 confers cold tolerance through promoted polyamine turnover, antioxidant protection, and proline accumulation. Abstract : A cold responsive ethylene responsive factor from Medicago falcata up‐regulates the genes associated with polyamine synthesis and catabolism, promotes polyamine turnover, antioxidant protection, and proline accumulation, and confers cold tolerance.